(untitled) (Research, Society and Development, 2020)
Objective: To evaluate the frequency of pressure injuries and associated factors in the older pacients with gastrointestinal cancer. Methods: Cross-sectional study of 212 individuals aged 60 years and older and diagnosed with untreated gastrointestinal cancer confirmed by histology, cytology or immunohistochemistry. Patients who had undergone previous cancer treatment, except surgical ones, were excluded. The variables studied were: pressure injury, nutritional status, weight loss in the three months prior to the assessment, functionality, level of physical activity, presence of comorbidities and laboratory variables. For media comparisons, Student’s test and categorical variables or square test or Fisher’s exact test were used. In the multivariate analysis using logistic regression, the Wald test was used to evaluate the independent effects of factors with p <0.20 and applied to the Hosmer-Lemesho test. Results: The frequency of LP was 68/212 (32.1%). In the multivariate analysis, variables that may remain associated with the presence of LP were: hypertension and cerebrovascular disease. The final model presents an adequate fit to the data (Hosmer-Lemeshow test (p = 0.736). Conclusion: these findings can guide future research and can serve as a guide in health care services decisions about the use of pressure injury prevention strategies.